Analysis of Vacancies in Agricultural Specialties in the Labor Market of the Ural Federal District - Valentina SHARAPOVA; Natalia SHARAPOVA; Yuri SHARAPOV; Ivan BORISOV (Communications of International Proceedings, 2020)
The article deals with the topical issues of supply and demand for the labor of agricultural specialists. The study was based on the two most in-demand specialties: agricultural and tractor driver. The research was carried out on the basis of data from the official websites for job search, as well as data presented on the websites of the Labor and Employment Departments of the Ural Federal District. The purpose of the study is to analyze vacancies in agricultural specialties in the context of the introduction of professional standards. In the course of the research, the following methods were used: monographic research, analysis, synthesis, comparison, generalization.
Keywords: Supply and demand in the labor market; vacancies; wages; agronomist; tractor driver; professional standard.